Lactiplantibacillus plantarum KF511 ameliorates cigarette smoke extract and porcine pancreatic elastase-induced COPD via inhibition of MAPKs in mice - Gun-Dong Kim; Ji-Eun Eom; Young In Kim; Dong-Uk Shin; Kyung Min Lim; Hyeon-Ji Song; Eun Yeong Lim; Ju Hye Song; Ha-Jung Kim; Byeong Yeob Jeon; Kyung Hwa Song; Hee Soon Shin; et al. (Journal of Functional Foods, 2024)
Because diminished pulmonary function in chronic obstructive pulmonary disease (COPD) is not fully reversible, it is important to prevent and manage COPD through smoking cessation, reducing exposure to air pollutants, and a healthy diet with functional foods. Thus, to confirm the availability of Lactiplantibacillus plantarum KF511 as a functional food for lung health, we evaluated the alleviating effect of L. plantarum KF511 on lung injuries in a cigarette smoke extract and elastase-induced COPD mouse and phorbol 12-myristate 13-acetate-stimulated NCI-H292 cells. L. plantarum KF511 suppressed the immune cell infiltration and production of mucin, matrix metalloproteinases, cytokines, and chemokines in bronchoalveolar lavage fluid, and alleviated tissue damage and mucin hypersecretion in the lungs. In addition, L. plantarum KF511 inhibited the activation of mitogen-activated protein kinases in the lungs of COPD mice and NCI-H292 cells. These results suggest that L. plantarum KF511 is an effective probiotic supplement to prevent and manage respiratory diseases.